Differentiation and Individualization in the Professional Training of Future Physical Education Teachers for Organizing Individual Work with Pupils - Alieksieiev, Oleksandr (Pedagogical Discourse, 2025)
The article substantiates the essence, goals, and pedagogical mechanisms of differentiation and individualization in the professional training of future Physical Education teachers for organizing individualized work with students. The purpose of the study is to theoretically substantiate and reveal the essence of differentiation and individualization in the professional training of future physical education teachers, as well as to determine the pedagogical conditions and technological principles for forming their readiness to organize individual work with students. The study reveals a structural-functional model of developing the relevant professional competence, which includes motivational-value, content-operational, and reflective-evaluative components. Special attention is paid to the pedagogical conditions that ensure the effective implementation of differentiated and individualized approaches in the educational process of higher education institutions. The research emphasizes the importance of practice-oriented training, the integration of personalized learning technologies, and the formation of students’ readiness to analyze and respond to the individual needs, physical abilities, and educational trajectories of schoolchildren. The article also highlights the significance of reflective practices, diagnostic tools, and adaptive teaching methods that shape a teacher’s ability to design and conduct individualized physical education activities. The obtained results contribute to the modernization of educational programs, improve the quality of professional training, and strengthen the capacity of future teachers to implement student-centered approaches in contemporary school physical education. The findings may serve as a methodological basis for further research in professional education and for developing innovative models of teacher training aimed at supporting the holistic development of every learner.